Antisense RNA transcripts in the blood may be novel diagnostic markers for colorectal cancer - Kurokawa, Tomohiro (Oncol Lett, 2017)
Numerous genetic studies have been conducted regarding the occurrence of colorectal cancer (CRC) and the prognosis using microarrays. However, adequate investigations into the diagnostic application of microarrays have yet to be performed. The simplicity and accuracy of diagnosis and prognosis tracking are important requirements for its processes, and the use of blood cells for diagnosis is considered to be suitable to meet these requirements. The patients involved in the study were 28 preoperative patients with CRC and 6 healthy individuals who served as controls. RNA was extracted from the blood cells of the patients and analyzed using a sense/antisense RNA custom microarray. In the patients with CRC, the expression levels of 20 sense RNA and 20 antisense RNA species were identified as being significantly altered compared with that of the healthy volunteers (P<0.05; fold-change, >2.0). Cluster analysis of these RNA species revealed that the top 10 antisense RNAs significantly clustered patients with cancer and healthy individuals separately. Patients with stage I or II CRC exhibited significant changes in the expression levels of 33 sense and 39 antisense RNA species, as compared with healthy volunteers (P<0.01; fold-change >2.0). Cluster analysis demonstrated that patients with stage I or II CRC and healthy volunteers formed separate clusters only among the top 20 antisense RNA species. A tracking study of expression levels of haloacid dehalogenase-like hydrolase domain-containing 1 (HDHD1) antisense RNA was performed and a significant difference was identified between the CRC and healthy groups revealing that the levels at one week and three months following surgical removal of the cancerous tissue, decreased to almost same levels of the healthy individuals. The results of the current study indicate that HDHD1 antisense RNA may serve as a potential biomarker for the prognosis of CRC.